The Importance of Neurophysiology in the Study of Predators and Herbivores: A Neuroecological Perspective - Hasan, Hasanain Mohammed (Universitas Muhammadiyah Sidoarjo, 2025)
Predator–herbivore interactions are central to ecological dynamics, shaping species evolution, population stability, and ecosystem function. Recent advances in neurophysiology have revealed mechanistic layers underlying these interactions, encompassing sensory processing, stress and fear responses, decision-making, learning, and memory. This review synthesizes findings from the past five years to highlight how neural circuits mediate predator detection, prey evasion, and adaptive behaviors, emphasizing individual variation, sex differences, and developmental plasticity. We discuss sensory neurophysiology in both predators and herbivores, showing how multimodal integration, context-dependent processing, and plasticity influence behavior in natural environments. Stress neurobiology and fear responses are explored, illustrating the role of the hypothalamic–pituitary–adrenal axis, limbic circuits, and neurotransmitter dynamics in shaping acute and long-term responses to predation risk. Decision-making, learning, and memory are examined as mechanisms by which experience modifies predator and prey strategies, with implications for co-evolution and ecological fitness. Evolutionary and ecological implications are considered, including the role of neurophysiology in driving selective pressures, shaping trophic interactions, and mediating non-consumptive effects that influence community structure. Finally, we highlight emerging technological advances—such as portable neural imaging, electrophysiology, genomic analyses, and machine learning approaches—that enable integration of neurophysiological data with behavioral and ecological research. Understanding these neurobiological mechanisms not only uncovers hidden layers of predator–herbivore dynamics but also provides actionable insights for wildlife management, conservation planning, and ecosystem restoration. By bridging mechanistic neuroscience with ecological and evolutionary theory, this review emphasizes the value of neurophysiology as a critical tool for predicting behavioral responses and resilience in changing environments. Highlights Neurophysiology reveals how sensory processing, stress circuits, and learning mechanisms shape predator detection, prey avoidance, and behavioral adaptation. Predator cues drive significant neural and hormonal responses—often sex-specific and long-lasting—that influence decision-making and ecological fitness. Integrating neural mechanisms with ecological models enhances predictions of predator–herbivore dynamics, especially under environmental and anthropogenic change.